A convenient method for reduction dehalogenation of α-halocarbonyl compounds using benzenethiol in K+/CH3CN system. (2nd July 2016) - Dong, Wei-Li; Cai, Wen-Xi; Wu, Rui; Li, Zheng-Ming; Zhao, Wei-Guang; Liu, Xing-Hai
GRAPHICAL ABSTRACT: ABSTRACT: Benzenethiol, as a reductive agent for the dehalogenation of various α-halocarbonyl compounds, is investigated in the K + /CH3 CN system. The reaction affords the reduced compounds in high yields under mild reaction conditions, especially α-chlorocarbonyl compounds. Furthermore, the reaction performed under ultrasonic irradiation greatly shortens the reaction time.